KEANEKARAGAMAN JENIS IKAN TANGKAP DI SEKITAR KARAMBA DAERAH NGASINAN WADUK KEDUNGOMBO JAWA TENGAH - Anang Yunianto; Sapto Punomo Putro; Riche Hariyati (Jurnal Akademika Biologi, 2012)
Nowadays the fish farming activity in the Kedungombo reservoir tends to increase gradually. The knowledge of diversity and abundance of  fish species would be usefull to preserve the ecosystem of the reservoir. The improving management of water resources reservoirs is also needed to increase the economy of local community. The purpose of this study is to determine the diversity and abundance of fish found in the area around Kedungombo reservoir. The study is explorative. Sampling was done randomly at 5 stations. Data analysis was done to determine the similiaritas index (Di), diversity index (H '), evenness index (e), relative abundance. Hutcheson t test was carried out to determine differences in species diversity at July and August with five-point observation stations.  Based on the results of the study, during the months of July to August, there are 8 species, namely: Silver barb (Barbonymus gonionotus), tilapia (Oreochromis niloticus), Mujair (Oreochromis mossambicus), catfish (Pangasius sutchi), Betutu (Oxyeleotris marmorata), Red Devil (Amphilophus labiatus), Redoson (Trichogaster trichopterus) and Gurame (Osphronemus goramy). The level of diversity and evenness of fish are considerably low. Silver barb fish dominated in relative abundance. Hutcheson t test results showed no difference in fish species diversity, indicated by t count <t table at the 95% confidence level. Water quality, light brightness and sediments were considered as a suitable habitat for fish. This study implies that other studies at the other regions are needed to assess the diversity of tropical fish